Language Matters: Exploring Preferred Terms for Diverse Populations - Higinio Fernandez-Sanchez; Emmanuel Akwasi Marfo; Diane Santa Maria; Mercy Mumba (SAGE Publishing, 2024)
This article explores the significance of employing preferred terms and inclusive language in research practices concerning diverse populations. It highlights how inappropriate terminology can lead to labeling, stereotyping, and stigma, particularly for equity-denied groups. The study aimed to identify and analyze terminology preferences for diverse communities by major international organizations. Through a systematic environmental scan methodology, data were collected from 12 prominent organizations. The results indicate a concerted effort toward adopting inclusive language, with organizations favoring respectful and accurate terminology. For instance, terms like "people made vulnerable by systemic inequities" and "migrant workers" were preferred over outdated or stigmatizing alternatives. The discussion emphasizes the importance of identifying conflicting terms and trends in terminology preferences over time. We recommend prioritizing the use of preferred terms to promote respectful and accurate discourse, with a focus on person-centered language. Ultimately, the findings underscore the critical role of language in shaping perceptions and attitudes toward diverse communities, and advocate for continued efforts to promote inclusivity and equity in research, policy, and practice.